Verifying OpenJDK’s LinkedList using KeY (extended paper) - Hiep, Hans-Dieter A.; Maathuis, Olaf; Bian, Jinting; de Boer, Frank S.; de Gouw, Stijn (International journal on software tools for technology transfer, 2022)
As a particular case study of the formal verification of state-of-the-art, real software, we discuss the specification and verification of a corrected version of the implementation of a linked list as provided by the Java Collection Framework.